2019
DOI: 10.1007/s11606-019-04946-3
|View full text |Cite
|
Sign up to set email alerts
|

Milestone Implementation’s Impact on Narrative Comments and Perception of Feedback for Internal Medicine Residents: a Mixed Methods Study

Abstract: BACKGROUND: Feedback is a critical element of graduate medical education. Narrative comments on evaluation forms are a source of feedback for residents. As a shared mental model for performance, milestone-based evaluations may impact narrative comments and resident perception of feedback. OBJECTIVE: To determine if milestone-based evaluations impacted the quality of faculty members' narrative comments on evaluations and, as an extension, residents' perception of feedback. DESIGN: Concurrent mixed methods study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…The ACGME intends for Milestones to be ''narratives, not numbers'' 21 ; meaningful narrative comments are the key to moving past average numerical assessment data. Although there are limitations to narrative comments, including that they may not cover the full breadth of subcompetencies 22 or may lack sufficient detail, 23 our participants noted that they can be helpful in corroborating or adjusting numerical scores.…”
Section: Discussionmentioning
confidence: 90%
“…The ACGME intends for Milestones to be ''narratives, not numbers'' 21 ; meaningful narrative comments are the key to moving past average numerical assessment data. Although there are limitations to narrative comments, including that they may not cover the full breadth of subcompetencies 22 or may lack sufficient detail, 23 our participants noted that they can be helpful in corroborating or adjusting numerical scores.…”
Section: Discussionmentioning
confidence: 90%
“…28,43 Evidence that Milestones and entrustable professional activities (EPAs) provide mental models shared between assessors and learners is mixed. 33,[44][45][46][47][48][49] Part of the challenge is structural: Milestones and EPAs that are broadly defined are susceptible to variable interpretation. 49,50 This variability is affected by the larger challenge of the lack of an SMM of any instrument of assessment and the consequences of that assessment, which involves a process akin to negotiation.…”
Section: Challengesmentioning
confidence: 99%
“…49,50 This variability is affected by the larger challenge of the lack of an SMM of any instrument of assessment and the consequences of that assessment, which involves a process akin to negotiation. 45,46,51 The most important step in developing, maintaining, and using SMMs is to first acknowledge the complexity of a seemingly simple concept. Mental models are like Russian nesting dolls with each successive underlying model giving form to the next.…”
Section: Challengesmentioning
confidence: 99%
“…11,14 Facilitated Self-Reflection Simply providing assessment data, including the detailed Milestones narratives, to the trainee without conversation can be unhelpful and frustrating. 18,19 Kluger and DeNisi's review of feedback interventions demonstrated that feedback can be harmful or at best unproductive depending on the intervention. 20 Additional research from the health services domain revealed that providing quality data without support or guidance has minimal effects on behavioral change.…”
Section: Role Of Iterationmentioning
confidence: 99%